Pengaruh Reputasi Auditor Dan Komite Audit Terhadap Nilai Perusahaan Basic Materials Yang Terdaftar Di Bei Periode 2018-2021 - Muren, Louis Albertoaran; Pangaribuan, Hisar (Bongaya Journal of Research in Accounting (BJRA), 2023)
The purpose of this study was to observe and determine the effect of the reputation of the auditor and the audit committee on the value of basic materials companies listed on the Indonesia Stock Exchange for the period 2018-2021. This study uses quantitative methods, the sample used is 45 companies using the purpose sampling method, totaling 180 data. The technique used in this research is descriptive statistical technique, classical assumption test, t hypothesis test, f hypothesis test, and coefficient of determination test. Based on the results of the t hypothesis test, it explains that the reputation of the auditor has a significant effect on firm value. While the audit committee does not have a significant effect on firm value. Therefore, it can be said that there is no substantial effect on firm value on the auditor and audit committee reputation variables, either one or both variables.